Finding Greater Value in the Fourth Year of Medical School: Accelerating the Transition to Residency. (April 2020) - Pellegrini, Vincent D.; Franks, Adam M.; Englander, Robert
Abstract : The recent focus on competency-based medical education has heralded a true change in U.S. medical education. Accelerating the transition from medical school to residency may reduce student debt, encourage competency-based educational advancement, and produce residency graduates better prepared for the independent and unsupervised practice of medicine. With some purposeful design considerations, innovative time-variable programs or fixed-time accelerated tracks can be implemented within current regulatory parameters and without major alteration of existing institutional regulatory guidelines, state licensing requirements, or specialty certification requirements. Conferring an MD degree in less than 4 full academic years provides opportunities to customize and find greater value in the fourth year of medical school as well as to redeploy time from undergraduate medical education to graduate medical education; this could shorten the overall time to completion of training and/or provide for customization of training in the final years of residency. In this article, the authors discuss the regulatory requirements for successful implementation; consider issues related to "off-cycle" graduates advancing to residency training outside of the Match; and share examples of 3 innovative accelerated programs in pediatrics, family medicine, and orthopaedics that have yielded advantages to individual learners, including reduced educational debt, as well as to the health care system.